LIVING ISLAMIC PHILOSOPHY: Reflection on Mulyadhi Kartanegara's Thought - Nuruddin Al Akbar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This study elaborates Mulyadhi Kartanegara's thoughts regarding the continuity of Islamic philosophy after the Ibn Rushd era. This research is a case study-based qualitative research using a review on Kartanegara's travel notes and research reports as the object. This research also uses other relevant studies to understand Kartanegara’s big idea. This study concludes that, although the idea on Islamic Philosophy does not perish in the Iranian region has been a thesis recognized by many researchers, Kartanegara explore further the dynamics of Islamic philosophical traditions in Iran since the post-Ibn Rushd era. He was dissatisfied with the explanations of many experts who emphasized the elaboration of a prominent philosopher, Mullâ Sadrâ, while ignoring the role of minor philosophers in supporting the continuity of the Islamic philosophical tradition in Iran. This research found, Kartanegara could construct the argument that Islamic philosophy is a living tradition marked by the continuity of ideas developed by minor and major philosophers. Mulyadhi also showed that Islamic philosophy has relevance for overcoming contemporary challenges, primarily related to the problem of knowledge production.